EXPLOITING THE COGNITIVE-PHYSICAL-EMOTIONAL INTERCONNECTION: MOTOWORDS AND THE DISTAL METHOD - Konstantinos G. Papageorgiou (Scientific Publishing House. NSA Press, 2020)
Background: communication between trainer and athlete has been studied in terms of feedback, but not in terms of codifying information for instruction; here implications for cognition and cognitive skills are also discussed. Purpose: to present a new tool, motowords, a tool for verbal codifi cation between athlete and trainer that also provides a number of incidental benefi ts: it helps adjust the Degrees of Freedom & Contextual Interference of a drill, it employs cognitive functions, fosters active participation of the athlete, and bridges the gap between serial and random practice. Moreover, we intend to theorize how the positive effects of motowords are multiplied when combined with drill-synthesis and drill-structure, in addition to differentiated (self)training, concepts that aim at increasing the ecological validity of training sessions. Method: the theoretical background supporting the effectiveness of these tools is discussed. Leads: to a broader vision about the important role of cognitive and emotional skills within a holistic context, aiming at developing "literate" individuals rather than just motor experts, both of which are at the very core of the Distal Method for expertise attainment.